Identity Creating Goods and Free Trade - Gerhard Clemenz (Verein für Socialpolitik, 2010)
Identity creating or cultural goods are characterized by a positive consumption network externality and increased utility because of doing what the reference group expects. Different countries have different cultural goods. It is shown that moving from autarky to free trade a country may suffer a welfare reduction if consumption of its own cultural good is reduced in favor of a foreign cultural good, regardless of comparative advantage. On the other hand, welfare may be increased even if the domestic cultural good disappears altogether.
Keywords: F10; F19; F13; 330; Cultural goods; free trade